Na-neun No-rae-ha-go Shi-peo - Oh, Jung-hun (South Korea, 2012)
The multicultural singing group ‘Montant’ consisting of foreign migrants to Korea and Koreans are busy preparing their first promotional performance in December. Members from Myanmar, the Philippines, Indonesia, China get together every day to practice their vocals and create new songs. Although they are still awkward with the language and Korean culture, they are a happy group collaborating in this foreign country to create harmony.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films